Moving Development and Security Narratives a Step Further: Human Security in the Human Development Reports. Issue 1 (2nd January 2016) - Gomez, Oscar A.; Gasper, Des; Mine, Yoichi
Abstract : During the last 20 years, the idea of human security has been spreading globally and locally, albeit unevenly. One factor in this growth has been the role of Human Development Reports as sources of alternative narratives to understand social problems and progress. This paper describes how National and Regional Human Development Reports have generated a rich and analytically fruitful set of approaches to examining and responding to contextual threats, following human security principles – for people-centred, comprehensive, context-specific and prevention-oriented analysis and exploring basic security questions. However, this richness has not fed back yet into the global apex of Human Development Reports and related work, reflecting a disconnection between levels of analysis that hinders the transformation of development and security narratives.